2021
DOI: 10.23910/1.2021.2656a
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils: An Effective Therapeutic Strategy against SARS-CoV-2

Abstract: Thousands of individuals have perished as a result of Covid-19 and it has turned into a global problem. The novel coronavirus 2019 (nCoV-2019), also known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has spread rapidly following its discovery in Wuhan patients with acute pneumonia in China. No medication or vaccine are available to treat human coronavirus infection successfully. The alternative therapies and cures are not are effective or authorised to treat Corona virus. Treatments are pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Significantly, the antiviral activities of essential oils are their ability to break down viral membranes easily due to their lipophilic nature and to interfere with the virus's life cycle by affecting host-virus connections. 3,29,30 Synergistic interactions between essential oils and synthetic antiviral agents have also been reported in some publications. 31 In light of current information, many approaches based on essential oils and their components have been proposed for treating COVID-19 and might become strong medication candidates.…”
Section: Antiviral Activities Of Essential Oilsmentioning
confidence: 88%
See 1 more Smart Citation
“…Significantly, the antiviral activities of essential oils are their ability to break down viral membranes easily due to their lipophilic nature and to interfere with the virus's life cycle by affecting host-virus connections. 3,29,30 Synergistic interactions between essential oils and synthetic antiviral agents have also been reported in some publications. 31 In light of current information, many approaches based on essential oils and their components have been proposed for treating COVID-19 and might become strong medication candidates.…”
Section: Antiviral Activities Of Essential Oilsmentioning
confidence: 88%
“…61 The main chemical components of T. vulgaris essential oil are thymol and carvacrol, besides p-cymene (8.41%), γ-terpinene, caryophyllene, spathulenol, germacrene D, β-phenyl alcohol, and δ-terpineol. 30,43 Antibacterial and antifungal effects of the essential oil were observed against Gram(+) & Gram(-) bacteria and fungal strains. 62 In in silico studies, carvacrol and thymol were found to be effectively binding to Mpro of SARS-CoV-2.…”
Section: Family: Geraniaceaementioning
confidence: 99%
“…Table S1). Medicinal plants like Glycyrrhiza glabra, Andrographis paniculata, Withania somnifera, Tinospora cordifolia, herbs used in cooking like Z. officinale, Allium sativum, Moringa oleifera, Piper nigrum, Cinnamomum verum, Curcuma longa, and essential oil-bearing plants like Ocimum sanctum, Azadirachta indica, Syzygium arromaticum, Eucalyptus globulus (Palai and Kesh, 2021) possesses phytochemicals having antioxidant, antiviral, and immunomodulatory properties (Fig. 1, Suppl.…”
Section: Vati Vyosadimentioning
confidence: 99%